Regent Park : A Study in Slum Clearance - Rose, Albert, 1917- (Book collections on Project MUSE., 1958)
More than ten years of study of the problem of slum clearance in Toronto, plus participation in the planning and execution of the Regent Park project, provided the author with an exceptional opportunity to know thoroughly the materials of his study.